A Decade of Radical Pedagogy: Barry McNeill and Environmental Design in Tasmania, 1969–79. Issue 3 (2nd September 2018) - King, Stuart; Owen, Ceridwen
ABSTRACT: Recent scholarship on pedagogical experimentation in the 1960s and 1970s has identified a diverse field of practices brought to bear on architectural education and their influence on architectural discourse. A new Environmental Design programme in Hobart, Tasmania, led by Barry McNeill (1937–2014) from 1969 to 1979, sits among these projects. It was the first Environmental Design programme in Australia and the most complete and radical transformation of an architecture and planning curriculum in Australia at the time, proactively embracing the educational ideals sought by student activists regionally and globally. Employing records from McNeill's private archive and related archives alongside interviews with former staff and students, this article examines and places McNeill's critical social approach to architectural education within the wider field of experimental architectural educational practices of the era. It explores the specific constellation of conditions that enabled McNeill's radical transformation of curriculum in Hobart, as well as its subsequent circulation and influence beyond Tasmania, highlighting the circuitous flows of ideas during the period. The article proposes McNeill's Environmental Design programme as a space where international models from the USA, UK, and beyond were channelled, tested, contextualised, and transformed.